Respuesta :
-3x from both sides
-4y = 6-3x
Divided -4 from both sides
Y = 6-3x/-4
Y = -3/2 + 3/4x
-4y = 6-3x
Divided -4 from both sides
Y = 6-3x/-4
Y = -3/2 + 3/4x
Hey there! :)
3x - 4y = 6 ; solve for y.
To solve for y, we must isolate this variable. To do this, we must remove any other numbers/variables that do not contain a y variable in it.
So, our first step is to subtract 3x from both sides.
3x - 4y - 3x = 6 - 3x
Simplify.
-4y = -3x + 6
Then, divide both sides by -4.
-4x ÷ -4 = (-3x + 6) ÷ -4
Simplify.
x = 3/4x - 6/4
Simplify.
x = 3/4x - 3/2
~hope I helped~